2014
DOI: 10.1080/19440049.2014.940608
|View full text |Cite
|
Sign up to set email alerts
|

Energy drink consumption and impact on caffeine risk

Abstract: The impact of caffeine from energy drinks occurs against a background exposure from naturally occurring caffeine (coffee, tea, cocoa and foods containing these ingredients) and caffeinated beverages (kola-type soft drinks). Background caffeine exposure, excluding energy drinks, was assessed for six New Zealand population groups aged 15 years and over (n = 4503) by combining concentration data for 53 caffeine-containing foods with consumption information from the 2008/09 New Zealand Adult Nutrition Survey (ANS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
2
15
0
1
Order By: Relevance
“…The majority (99.1%) of tertiary students who participated reported regularly consuming at least one source of caffeine in their diet. This is higher than the estimated 88% of NZ adults (≥15 years-old) previously reported in the NZ Adult Nutrition Survey 2008/09 (NZ ANS08/09) [ 17 ] and higher than rates of caffeine consumption in the USA (89%) [ 49 ]. Other studies which have examined caffeine consumption in tertiary students show the majority (87.8–98%) regularly consume caffeine from one or more sources [ 50 , 51 , 52 , 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…The majority (99.1%) of tertiary students who participated reported regularly consuming at least one source of caffeine in their diet. This is higher than the estimated 88% of NZ adults (≥15 years-old) previously reported in the NZ Adult Nutrition Survey 2008/09 (NZ ANS08/09) [ 17 ] and higher than rates of caffeine consumption in the USA (89%) [ 49 ]. Other studies which have examined caffeine consumption in tertiary students show the majority (87.8–98%) regularly consume caffeine from one or more sources [ 50 , 51 , 52 , 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 64%
“…Over a third of caffeine consumers ( n = 108, 34.4%) exceeded the ‘adverse effect level’ of 3 mg·kgbw −1 ·day −1 [ 17 ]. Smokers were 3.34 times more likely to exceed this level than non-smokers (χ 2 (1) = 15.680, p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enerji içeceklerinin enerji sağlayarak performans arttırdığı, yorgunluğu azalttığı ve dikkati arttırdığı gibi söylemler ile özellikle gençler arasında tüketimi hızla yaygınlaşmıştır [16][17][18]. Ancak yapılan çalışmalar neticesinde terapötik etkisinin olmadığı, farmakolojik etkiler ve toksisitesinden ötürü özellikle çocuklarda ciddi sorunlara neden olabileceği bildirilmiştir [19]. Avrupa'da 1987 yılında piyasaya girerek 1997 yılında enerji içeceği üreten firmaların tanıtımları ile birçok ülkeye yayılmıştır [20].…”
Section: Enerji İçecekleriunclassified
“…Reported energy drink consumption rates within those >18 y range from 3% to 60%, varying by population and manner of assessment [ 17 20 ], with consumption rates having dramatically increased over the last two decades [ 11 , 20 ]. Questionnaire-based surveys reported that university students who consumed energy drinks within the last 30 days, or on average one per month, range from 11% to 70% [ 6 , 21 – 28 ].…”
Section: Introductionmentioning
confidence: 99%